2017
DOI: 10.1016/j.neuro.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic alterations of ultrasonic vocalization in rat pups induced by perinatal hypothyroidism

Abstract: Perinatal hypothyroidism causes serious damage to auditory functions that are essential for vocalization development. In rat pups, perinatal hypothyroidism potentially affects the development of ultrasonic vocalization (USV) as a result of hearing deficits. This study examined the effect of perinatal hypothyroidism on the development of USVs in rat pups. Twelve pregnant rats were divided into three groups and treated with the anti-thyroid drug methimazole (MMI) via drinking water, from gestational day 15 to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Previous studies have elucidated the developmental changes in the acoustic characteristics of USV emitted by rat pups upon maternal isolation (Kehoe & Harris, 1989;Elsner et al, 1990;Brudzynski et al, 1999;Schwarting & Wohr, 2012;Kromkhun et al, 2013;Wada, 2017) and reported that the number of USVs increases on PNDs 3-5 to reach a…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have elucidated the developmental changes in the acoustic characteristics of USV emitted by rat pups upon maternal isolation (Kehoe & Harris, 1989;Elsner et al, 1990;Brudzynski et al, 1999;Schwarting & Wohr, 2012;Kromkhun et al, 2013;Wada, 2017) and reported that the number of USVs increases on PNDs 3-5 to reach a…”
Section: Discussionmentioning
confidence: 99%
“…USVs are generated by high-pressure air flow from the thorax through a small orifice located in the closed vocal folds (Brudzynski & Fletcher, 2010). An increase in the rate of development of the size and length of the larynx and vocal tract would be expected to produce lower fundamental frequencies of USVs, which has been previously reported to occur as rat pups age (Elsner et al, 1990;Wada, 2017).…”
Section: Effects Of Ethanol On Peripheral Vocalization-related Organsmentioning
confidence: 93%
See 1 more Smart Citation
“…Mice are also born deaf, but their auditory function begins around postnatal day 10, which is when the number of USVs in produced by mice sharply decreases (Ehret, 2005;Wiaderkiewicz et al, 2013). The hypothyroid rat pups weighed significantly less than controls (Wada, 2017), though, so this may also reflect a difference in sound production from potentially underdeveloped vocal cords. Although we have not noted any differences in body weight due to BPA exposure at this dose, several studies have reported that BPA may disrupt thyroid hormone function (Chevrier et al, 2013;Sheng et al, 2012).…”
Section: Ultrasonic Vocalizationsmentioning
confidence: 87%
“…The mechanism behind the increase in median frequency and call duration in BPA pups reported in chapter two is unclear. In a recent study in rats, perinatal hypothyroidism affected the acoustic characteristics and developmental timeline of pup USVs during isolation (Wada, 2017). Production of USVs decreases after auditory function develops, but the hypothyroid pups continued vocalizing after this point, indicating an auditory developmental delay.…”
Section: Ultrasonic Vocalizationsmentioning
confidence: 91%